Why Is Oral Phenylephrine on the Market After Compelling Evidence of Its Ineffectiveness as a Decongestant?. Issue 11 (November 2022) - Hatton, Randy C.; Hendeles, Leslie
Ineffective over-the-counter (OTC) drugs should be removed from the US market. Despite solid research showing that oral phenylephrine is ineffective as a decongestant, the US Food and Drug Administration has failed to respond to a 2015 citizen's petition to remove it from the OTC nasal decongestant monograph. Other examples of scientifically proven ineffective OTC medications include guaifenesin as an expectorant, dextromethorphan as a cough suppressant, and chlorpheniramine for cold symptoms.